2011
DOI: 10.1111/j.1467-9779.2011.01517.x
|View full text |Cite
|
Sign up to set email alerts
|

The Limited Power of Voting to Limit Power

Abstract: In this paper, we experimentally approach the question of which aspects of a voting procedure are able to restrict elected candidates' willingness to use their power in an opportunistic way. For this purpose, we rule out re-election concerns and analyze whether the presence of a vote by itself matters for the exercise of power. We compare two kinds of electoral campaigns: self-descriptions of personality and promises regarding prospective in-office behavior. We find that social approval as conveyed by a vote d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…In response, and aided by incentive-compatible mechanisms, economists step back to the lab to disentangle motivations within controlled settings. In lab experiments with student subjects, Corazzini et al (2014) allowed candidates to make promises to voters about how they will divide the pie that the election winner receives between themselves and the voters, and found that campaign promises may not be purely cheap talk (also see Corazzini et al 2007;Geng et al 2011).…”
Section: Related Literature and Motivationmentioning
confidence: 99%
“…In response, and aided by incentive-compatible mechanisms, economists step back to the lab to disentangle motivations within controlled settings. In lab experiments with student subjects, Corazzini et al (2014) allowed candidates to make promises to voters about how they will divide the pie that the election winner receives between themselves and the voters, and found that campaign promises may not be purely cheap talk (also see Corazzini et al 2007;Geng et al 2011).…”
Section: Related Literature and Motivationmentioning
confidence: 99%
“…Empirical Our paper builds on the assumption of heterogeneity with respect to lying aversion. Geng et al (2011) and Corazzini et al (2014) have recently shown in lab experiments that campaign promises may not be pure cheap talk. 4 In their experiments, candidates make promises to voters about how they will split a pie that the election winner receives between themselves and the voters.…”
Section: Related Literaturementioning
confidence: 99%
“…While a theoretical analysis based on the traditional assumption that candidates are completely selfish suggests that they will promise anything to get elected and once in office maximize their private gains (e.g., Alesina, 1988), it has recently been demonstrated by Geng et al (2011) and Corazzini et al (2014) that campaign promises are not just cheap talk even in one-shot interactions. Instead, most subjects in these experiments care about the deviation of their actions in office from their promises at the election stage.…”
Section: Introductionmentioning
confidence: 99%
“…Any individual who is sufficiently averse to this discomfort may therefore refrain from taking the action in the first place. Guilt aversion is able to explain a vast array of behaviors, including cooperation (Miettinen and Suetens, 2008), altruism (Andreoni and Rao, 2011), conformism (Khalmetski, 2015), group favoritism (Güth et al, 2009) and reciprocity (Chang et al, 2011), and economic experiments indicate that it is indeed an important determinant in a variety of different situations (Ketelaar and Au, 2003;Charness and Dufwenberg, 2006;Hopfensitz and Reuben, 2009;Geng et al, 2011;Battigalli et al, 2013). More recently, guilt averse behavior has also made its way into macroeconomic modeling.…”
Section: Introductionmentioning
confidence: 99%